A Comparison of the Clean Surplus and Prospect Theory Valuation Models - Swanson, Zane L.; Alltizer, Richard (Journal of Management Policy and Practice, 2019)
This study investigates the explanatory power of the clean surplus versus prospect theory valuation models. Literature argues the approaches are consistent from a theoretical perspective (Levy, De Giorgi and Hens 2012). To the authors’ knowledge, this the first empirical study to compare comprehensively these approaches, in particular, before and after the 2008 financial crisis. The clean surplus model appears to be a better predictor of firm value than prospect theory. The study is comprehensive with base case analyses, and model performance in regards to growth options, size/risk factors, and the pre/post 2008 crash periods.